Islam and contraception in urban North India - Muslim women's reproductive health behavior and decision-making - Weigl-Jäger, Constanze (Interdisziplinäre Zeitschrift für Südasienforschung, 2016)
This paper is based on ethnographic research conducted in a predominantly Muslim community in South Delhi. It analyzes the reproductive health behavior and decision-making of low-income Muslim women by focusing in particular on the context, in which the lives of these women are embedded. Fieldwork methods were participant observation, life histories and the conduction of in-depth interviews with forty women as well as medical practitioners and non-governmental/governmental health workers.It is shown that particularly socio-economic constraints as well as women’s poor state of health are the main factors influencing women’s reproductive decision-making. Women’s perception of reproductive health behavior is also closely intertwined with the existing social context and its related social and cultural norms. Local religious beliefs and practices however play a less significant role in determining women’s fertility decisions. Building on case studies of women who articulate their motivations regarding contraceptive use, I argue that Islamic norms and reasoning are fashioned pragmatically. Women manipulate, adopt or reject Islamic legal tenets in regard to contraception to achieve their own goals. All these factors result in a decline of fertility.